Cerebral Venous Sinus Thrombosis in a Child with Idiopathic Nephrotic Syndrome: a case report - Silva,Ana Isabel Rodrigues (2018)
ABSTRACT Complications are rare in pediatric cases of idiopathic nephrotic syndrome (NS). Thromboembolism ranks among the most uncommon and difficult complications to diagnose, particularly in the first episode of NS, since clinical signs might be unspecific. This report describes the case of a 5-year-old girl with NS for the first time presenting with severe hypoalbuminemia (< 2g/dL). The patient responded poorly to therapy with corticosteroids. On day 8 of hospitalization she started having headaches and vomiting; she did not present hemodynamic alterations, fever or exanthems, and her neurological parameters were normal. The patient was suspected for intracranial hypertension, and computed tomography scans revealed she had cerebral venous sinus thrombosis (CVST). She was started on anticoagulants and showed clinical signs of improvement. The patient had no evident prothrombotic risk factors. She had three other episodes since she was diagnosed, one in which her plasma antithrombin level was low. Although antithrombin levels were normal in her first episode, she was tested after the resolution of proteinuria. The low levels of antithrombin seen in the first recurrence might have mirrored the initial drop in plasma antithrombin levels, an idea supported by the severe hypoalbuminemia she had when diagnosed. This severe manifestation of acquired thrombophilia might be in the origin of CVST. This report presents a rare case of thromboembolic complication in a pediatric patient with NS. The patient progressed well since she was started on anticoagulants. Although she did not present any evident risk factors at first, the development of her case indicated that severe acquired thrombophilia might have worked as the pathophysiological mechanism leading to CVST.